Shakespeare Engraved: Frontispiece and Bardolatry - Sasaki, Kazuki (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
The term Bardolatry has been used for over a century to describe the adoration of an Elizabethan playwright, Shakespeare, but the causes of this phenomenon have not been fully elucidated. The study explores the nature of this worship produced and disseminated by various theatrical cultures during the long eighteenth century. To understand the formation of the phenomenon, this paper examines the shifts in the engraved frontispieces, taking The Tempest as an example.